Effects of ramp type demand and Weibull deterioration rate on retailers' optimal pricing and lot-sizing policies for deteriorating items with partial backlogging. (1st January 2011) - Valliathal, M.; Uthayakumar, R.
This paper discusses a deterministic inventory model for Weibull deteriorating items with partial backlogging under ramp type demand function. Shortages are allowed. Here we consider replenishment cycles, the time at which shortage begins; replenishment time and the optimal selling price are taken as decision variables. The objective of this model is to maximise the total profit (TP) which includes the sales revenue, purchase cost, the set up cost, holding cost, shortage cost and opportunity cost due to lost sales. We extend the results to ameliorating items also. Numerical examples are given to illustrate the model.